Primary production assessment of the Southern Indian Ocean in consumption of silicic acid - A.T. Kochergin (Ukrainian Antarctic Journal, 2014)
Estimation of the primary productivity (PP) for the area of the Southern Indian Ocean has been made on the base of assessment of interannual variability in concentration of silicic acid in the euphotic layer. Mean for different sublatitudinal zones (subtropical, subantarctic and antarctic) summary for the vegetative period and daily PP, varied in the range 13.0-29.8 and 0.03-0.23 g C m-2 relatively. Kerguelen Plato was the most productivity area, where summary PP reached 165 g C m-2 and daily - 0.9.